2012
DOI: 10.1007/s00572-012-0455-x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungal community differs between a coexisting native shrub and introduced annual grass

Abstract: Arbuscular mycorrhizal fungi (AMF) have been implicated in non-native plant invasion success and persistence. However, few studies have identified the AMF species associating directly with plant invaders, or how these associations differ from those of native plant species. Identifying changes to the AMF community due to plant invasion could yield key plant-AMF interactions necessary for the restoration of native plant communities. This research compared AMF associating with coexisting Bromus tectorum, an invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 62 publications
5
31
0
Order By: Relevance
“…However, a substantial portion of the fungal biomass is in the soil (Hart and Reader, 2002), and we therefore supplemented our fungal root colonization data with measurements of fungal biomarker concentrations in soil. Cheatgrass roots were poorly colonized by AMF (Table 1), and rhizosphere soil had the lowest concentration of AMF biomarker (Table 2), which supports previous findings that cheatgrass invasions can reduce overall AMF abundances (Al-Qawari, 2002;Busby et al, 2012). Knapweed, on the other hand, was highly colonized by AMF, and soil in knapweed invasions had the highest biomarker concentrations, which shows that invasive mycorrhizal forbs can be good hosts and enhance AMF abundances relative to native mixed plant communities (Greipsson and DiTommaso, 2006;Shah et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, a substantial portion of the fungal biomass is in the soil (Hart and Reader, 2002), and we therefore supplemented our fungal root colonization data with measurements of fungal biomarker concentrations in soil. Cheatgrass roots were poorly colonized by AMF (Table 1), and rhizosphere soil had the lowest concentration of AMF biomarker (Table 2), which supports previous findings that cheatgrass invasions can reduce overall AMF abundances (Al-Qawari, 2002;Busby et al, 2012). Knapweed, on the other hand, was highly colonized by AMF, and soil in knapweed invasions had the highest biomarker concentrations, which shows that invasive mycorrhizal forbs can be good hosts and enhance AMF abundances relative to native mixed plant communities (Greipsson and DiTommaso, 2006;Shah et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…The negative relationships between fungal OTU dominance and richness, and between fungal OTU dominance and AM colonization, suggest that competitive fungal taxa may reduce overall AMF richness and that these fungal taxa are more abundant in poorly colonized plants, such as grasses (Supplementary Table S6). Similar to Busby et al (2012), we found a higher AMF b-diversity in cheatgrass invasions and the grass-dominated native communities than in knapweed and spurge invasions (Supplementary Table S6, Supplementary Figure S3), which suggest a greater turnover among locations and an influence of stochastic processes in AMF community assembly within these plant communities.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, the performance of a model, native plant grown subsequently in these soils, was evaluated in the soil feedback pot experiment carried out under laboratory conditions. Understanding the interactions between invasive and native plants and AMF communities is fundamental to recognize the course and mechanisms of invasion and to yield key plant-AMF interactions necessary for the restoration of invaded areas (Busby et al 2013). …”
Section: Introductionmentioning
confidence: 99%